ASSESSMENT OF RADIATION IMPACT ON THE POPULATION OF FORMER URANIUM MINES - Damir A. Zaredinov; Marina V. Li; Otabek U. Eshmuradov (Central Asian Journal of Medicine, 2024)
The article presents the results of a study of the current radiation situation in the Yangiabad settlement of Tashkent oblast, which was founded as a working settlement for employees of uranium mines. As part of the research work, the equivalent dose rate of gamma radiation above the soil surface and the effective specific activity of natural radionuclides in soil samples taken in the surface 10-cm layer were measured. In the surveyed territories of Yangiabad settlement the EDR values in 2023-2024 were in the range from 0.10 µSv/h to 0.24 µSv/h, in children and adolescent institutions, polyclinics - from 0.10 µSv/h to 0.14 µSv/h, only in a few houses of private sector EDR reached values of 0.22-0.24 µSv/h due to construction materials. The main contribution to the effective specific activity of surface soil layers is given by radionuclides 232Th, 226Ra. Radiation situation in Yangiabad settlement of Tashkent region can be assessed as satisfactory, but it is not recommended to stay for a long time on the territories close to former uranium mines.